2007
DOI: 10.1021/jp075913v
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of Sodium, Potassium, and Chloride Ions in Solution and the Concept of Structure Maker/Breaker

Abstract: Neutron diffraction data with hydrogen isotope substitution on aqueous solutions of NaCl and KCl at concentrations ranging from high dilution to near-saturation are analyzed using the Empirical Potential Structure Refinement technique. Information on both the ion hydration shells and the microscopic structure of the solvent is extracted. Apart from obvious effects due to the different radii of the three ions investigated, it is found that water molecules in the hydration shell of K+ are orientationally more di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

106
588
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 630 publications
(718 citation statements)
references
References 37 publications
106
588
2
1
Order By: Relevance
“…Neutron scattering experiments conducted at ambient conditions have shown that pairing of Na + and Cl − ions is consistent with diffraction patterns even at modest concentrations. 33 Additional evidence of cluster formation in aqueous NaCl solution has been provided by dynamic light scattering and other computational studies (reviewed in Ref. 28).…”
Section: Resultsmentioning
confidence: 95%
“…Neutron scattering experiments conducted at ambient conditions have shown that pairing of Na + and Cl − ions is consistent with diffraction patterns even at modest concentrations. 33 Additional evidence of cluster formation in aqueous NaCl solution has been provided by dynamic light scattering and other computational studies (reviewed in Ref. 28).…”
Section: Resultsmentioning
confidence: 95%
“…Indeed, on account of its physico-chemical similarity to K + , a role for Na + as a generic, "benign" osmoticum in plant vacuoles is especially plausible and reasonable. However, differences in chaotropic and lyotropic properties of the two ions in terms of their effects on water and molecular structure, while controversial (Mancinelli et al 2007;Galamba 2012), may yet emerge as important to toxicity manifestations in intracellular compartments (Cheeseman 2013), and as a foundation for the maintenance of a high cytosolic K + /Na + ratio, although this has not yet been investigated stringently. A good number of the studies listed in Tables 1, 2, and 3 supports this notion.…”
Section: Sodium As a Nutrientmentioning
confidence: 99%
“…5 Geissler et al provided an interesting look into the complexity of an ionic dissociation and emphasized the importance of including explicit solvent dynamics. 4 One of the few quantum mechanical approaches to this topic was taken up by Ghosh et al 13 In their investigation of NaCl(H 2 O) [1][2][3][4][5][6] clusters and subsequent QM/EFP-MD simulation they found and described several Interionic Hydration Structures (IHS), in addition to the CIP and SSIP species.…”
Section: Introductionmentioning
confidence: 99%